Quodammodo alienum. Il testamento in scriptis di Enrico Detesalve (Genova, 21 settembre 1220) - Calleri, Marta (Scrineum, 2020)
Abundant literature exists on last wills and testaments, but very few consider solemn wills, since this type of document is very rare, as shown by the masters of the ars notariae of the thirteenth century. The 1220 in scriptis will of the Genoese Enrico Detesalve, which has come down to us in a fragment of the register of the notary Nicola Ferrarius, is one of the earliest examples of this type of will the few extant documents dating from the late Middle Ages. It attests to the Genoese notariate’s early rediscovery of the Roman legal heritage. After tracing the biographies of both notary and testator, the article provides an analysis of the document and its peculiar genesis.